A method for concentrating lipid peptide DNA and siRNA nanocomplexes that retains their structure and transfection efficiency - Tagalakis, Aristides D (Int J Nanomedicine, 2015)
Nonviral gene and small interfering RNA (siRNA) delivery formulations are extensively used for biological and therapeutic research in cell culture experiments, but less so in in vivo and clinical research. Difficulties with formulating the nanoparticles for uniformity and stability at concentrations required for in vivo and clinical use are limiting their progression in these areas. Here, we report a simple but effective method of formulating monodisperse nanocomplexes from a ternary formulation of lipids, targeting peptides, and nucleic acids at a low starting concentration of 0.2 mg/mL of DNA, and we then increase their concentration up to 4.5 mg/mL by reverse dialysis against a concentrated polymer solution at room temperature. The nanocomplexes did not aggregate and they had maintained their biophysical properties, but, importantly, they also mediated DNA transfection and siRNA silencing in cultured cells. Moreover, concentrated anionic nanocomplexes administered by convection-enhanced delivery in the striatum showed efficient silencing of the β-secretase gene BACE1. This method of preparing nanocomplexes could probably be used to concentrate other nonviral formulations and may enable more widespread use of nanoparticles in vivo.